Investigação da visão de profissionais acreditados à respeito de categorias da certificação LEED (Leadership in Energy and Environmental Design) aplicada na construção de edifícios - Silva, Arthur de Queiroz e (2015)
The construction industry plays an important role in the world economy and development, creating many direct and indirect labor, contributing to the advancement of infrastructure and reducing the dwelling deficit. However, this sector also directly relates to the three spheres of sustainability, affecting the occupant’s health and productivity over the built environment, consuming large energy, water and other natural resources levels, such as requiring spending on operating costs over the cycle life of the projects. In search of mitigating its impacts, several certifications of sustainability in buildings around the world appeared, acting as an evaluation and rating systems in the use of sustainable practices in construction of buildings. With a wide international recognition, the certification Leadership in Energy and Environmental Design (LEED) developed by the United States Green Building Council (USGBC), is held in Brazil by the Green Building Council Brazil (GBCB) certification body promoter and qualifier of the professional that operate in the Brazilian market for sustainable buildings. The research sought to contribute to a greater understanding of the LEED certification in Brazil through an analysis based on the perception and experience of professionals accredited by GBCB, featuring the categories of sustainability of this certification and identifying the most important factors in encouraging the sustainable buildings in country. The results showed that the category "Energy and Atmosphere" of the LEED certification is considered the most difficult in deployment and economic impact over buildings in the certification process, in addition, we found that factors that depend on public policies are the best ways for the development and realization of sustainable construction in the country.